2018
DOI: 10.21542/gcsp.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular outcomes following Kawasaki disease in Moscow, Russia: A single center experience

Abstract: Background: Awareness of Kawasaki disease (KD) is emerging in Russia but the diagnosis is still often missed.Methods: This is a retrospective study of 303 children with KD who received care at a single center in Moscow over the period from 2004 to 2016.Results: Overall, coronary artery aneurysms were documented in 91 (30,0%) of 303 patients and transient ectasia in 40 (13,2%). Intracoronary thrombi were found in 12 of 15 patients with giant aneurysms and in 3 patients with medium-sized aneurysms.Conclusion: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…This adds weight to our belief that the rise in observed incidence is not due to better case ascertainment, but due to a real increase in the number of cases and also case severity. Similarly high CAA rates have now also been observed in Sweden28 and Russia,29 with delayed diagnosis cited as a likely explanation for high coronary complication rates in the latter study. We found that the proportion with CAA was lowest in patients treated within 7 days, and this increased with later treatment.…”
Section: Discussionsupporting
confidence: 77%
“…This adds weight to our belief that the rise in observed incidence is not due to better case ascertainment, but due to a real increase in the number of cases and also case severity. Similarly high CAA rates have now also been observed in Sweden28 and Russia,29 with delayed diagnosis cited as a likely explanation for high coronary complication rates in the latter study. We found that the proportion with CAA was lowest in patients treated within 7 days, and this increased with later treatment.…”
Section: Discussionsupporting
confidence: 77%
“…Such children are at long-term risk of coronary thrombosis, acute coronary syndrome and progressive coronary stenoses 13–15. Comparably high rates of CAA have also recently been reported from Sweden, Russia, Germany and North America 16–18…”
Section: Introductionmentioning
confidence: 70%
“…Lyskina G at al. pointed that KD diagnosis is complicated due to the poor awareness of the disease among physicians in Russia [10]. The same issue may affect timely diagnosis of KD in Kazakhstan and Central Asia.…”
Section: Current Evidencementioning
confidence: 99%